Down regulating PHGDH affects the lactate production of sertoli cells in varicocele - Wen-bin Guo; Zhen-hui Huang; Cheng Yang; Xian-yuan Lv; Hui Xia; Hu Tian; Jian-kun Yang; Qi-zhao Zhou; Ming-kun Chen; Kang-yi Xue; Cun-dong Liu (BMC, 2020)
Abstract Background Although varicocele is considered to be one of the leading causes of male infertility, the precise mechanism underlying how varicocele leads to male infertility is not completely understood. We found the lactate concentration on the varicocele side of the patients was decreased compare with peripheral venous blood. In the testicles, the lactate produced by the sertoli cells through the glycolysis pathway provides most of the energy needed for spermatogenesis, the reduction of lactate will affect spermatogenesis. The objective of this study was to investigate the mechanism of this abnormal energy metabolism phenomenon in varicocele. Methods In this study, we collected the testicular tissue from patients with varicocele, the glycolysis related proteins PHGDH was identified by iTRAQ proteomics technology. Experimental rat varicocele model was constructed according to our new clip technique, the mRNA and protein expression levels of PHGDH were examined with qRT-PCR and Western blotting. We constructed a sertoli cell of PHGDH down-regulation model, and then detected the glucose consumption, LDH activities and lactate production in the sertoli cells. Western blot was conducted to investigate the effects of PHGDH on the expression of phosphoserine phosphatase (PSPH) and Pyruvate kinase M2 (PKM2). Flow cytometry was used to detect the cell apoptosis and cell cycle in sertoli cells. Results The results showed that testicular protein PHGDH was down-regulated in patients with varicocele and in experimental rat varicocele model. Down-regulation of PHGDH in sertoli cells significantly decreased the glucose consumption, LDH activities and lactate production in the sertoli cells, indicating that the low expression of PHGDH ultimately led to a decrease in lactate production by affecting the glycolysis. The Western blot results showed that the down-regulation of PHGDH significantly reduced the expression of pathway protein PSPH and PKM2, leading to the reduction of lactate production. Moreover, PHGDH knockdown can promote apoptosis and inhibit cell cycle to affect cell growth. Conclusions Overall, we conformed that varicocele lead to the decreasing of testis lactate production. Down-regulation of PHGDH in sertoli cells may mediate the process of abnormal glucose metabolism. Our study provide new insight into the mechanisms underlying metabolism-associated male infertility and suggests a novel therapeutic target for male infertility.